2008
DOI: 10.1002/pola.23196
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization kinetics of rac‐lactide initiated with alcohol/stannous octoate using in situ attenuated total reflectance‐fourier transform infrared spectroscopy: An initiator study

Abstract: Abstractrac‐Lactide polymerization kinetics in THF at 72 °C were monitored in real‐time using mid‐infrared ATR‐FTIR spectroscopy, with diamond composite insertion probe and light conduit technology. Monomer concentration as a function of time was acquired using the 1240 cm−1 resonance associated with the COOC stretch. Polymerizations were initiated with either n‐propanol (PrOH), ethylene glycol (EG), trimethylol propane (TMP), or pentaerythritol (PENTA) with the coinitiator stannous octoate (Sn(Oct)2). Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In view of the fast overall conversions observed for the ROTEP reactions performed by first allowing 2 to react 24 h with BnOH, we used in situ IR monitoring by React-IR to obtain accurate and precise kinetic data. Kinetic measurements of the ring-opening polymerization of LA using Sn­(oct) 2 were previously measured with React-IR using single-wavelength analysis. In preliminary experiments using this method we obtained variable and inconsistent results depending on the IR peak selected. This problem was avoided by using spectral deconvolution and global fitting in the 1900–900 cm –1 region to obtain relative amounts of rac -LA and PLA per spectrum collected.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the fast overall conversions observed for the ROTEP reactions performed by first allowing 2 to react 24 h with BnOH, we used in situ IR monitoring by React-IR to obtain accurate and precise kinetic data. Kinetic measurements of the ring-opening polymerization of LA using Sn­(oct) 2 were previously measured with React-IR using single-wavelength analysis. In preliminary experiments using this method we obtained variable and inconsistent results depending on the IR peak selected. This problem was avoided by using spectral deconvolution and global fitting in the 1900–900 cm –1 region to obtain relative amounts of rac -LA and PLA per spectrum collected.…”
Section: Resultsmentioning
confidence: 99%
“…One interesting aspect of the lactide ring‐opening reaction is the flexibility in designing different molecular architectures by employing multifunctional initiators. Different branched structures such as star‐shaped with arm numbers from 3 to 6, dendrimers, comb‐like, and barbell‐like molecules are synthesized by applying this strategy. An alternative procedure for the in situ synthesis of branched PLA is to use co‐monomers bearing initiation groups, such as 2,2‐ bis (hydroxymethyl) butyric acid in the presence of a tertiary amine, glycidol, and 5‐hydroxymethyl‐1,4‐dioxane‐2‐one .…”
Section: Introductionmentioning
confidence: 99%
“…The signicance of the relationships between macromolecule architectures and their properties has recently been recognized. Different polymer structures such as star-shaped with several arm numbers, [32][33][34][35] barbell-shaped, 36,37 comb-shaped, 38,39 and dendrimers 40,41 were synthesized. A lot of reports on the effect of branching, including branch structure and branch degree, showed that branching may accelerate or decelerate the crystallization process and inuence the melting behavior [42][43][44] and the rheological properties.…”
Section: Introductionmentioning
confidence: 99%